Building the Positive Emotion-Resilience-Coping Efficacy Model for COVID-19 Pandemic - Ke, Guek Nee; Grajfoner, Dasha; Wong, Rachel Mei Ming; Carter, Stephen; Khairudin, Rozainee; Lau, Wee Yeap; Kamal, Khalil Anwar; Lee, Shen Chieng (Frontiers in Psychology, 2022)
The world faces unprecedented challenges because of the Coronavirus Disease 2019 (COVID-19). Existing theories of human flourishing and coping efficacy are too broad and general to address COVID-19 unprecedented mental health challenges. This study examined two main objectives, first the associations between psychological outcomes (i.e., depression, anxiety, and stress) and psychological wellbeing of this phenomenon, and second, moderating and mediating factors emotions, resilience and coping self-efficacy. A nationwide survey was carried out on a Malaysian sample (n = 920). Participants completed an on-line survey that assessed psychological outcomes, psychological wellbeing, positive–negative emotions, resilience, and coping self-efficacy. The relationship between psychological states and psychological wellbeing was successfully mediated by coping self-efficacy (direct effects of −0.31 to −0.46 at p < 0.01) and resilience (direct effects of −0.06 to −0.26 at p < 0.01). Moreover, positive emotion significantly moderated depression (b = −0.02, p < 0.01) and anxiety (b = −0.14, p = 0.05) with psychological wellbeing. Findings highlighted the importance of these factors in developing a dedicated model to be built into the recovery plan to ameliorate the negative impact of COVID-19 on psychological wellbeing. Hence, the Positive Emotion-Resilience-Coping Efficacy Model was developed.